Convert each equation to Vertex Formula and Graph each equation showing its vertex. x2 − 5x + 6=0

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

Convert each equation to Vertex Formula and Graph each equation showing its vertex. x2 − 5x + 6=0

Mathematics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

vertex form -> y = a(x-h)^2 + k , (h,k) is the vertex point the standard form -> x^2 + bx +c = 0 x2 − 5x + 6=0 (x-3)(x-2) = 0 the graph intersect x-axis at x=3 and x=2 the value of h = 3+2/2 = 5/2 therefore k = (5/2)^2 -5(5/2) + 6 = 25/4 - 25/2 + 6 = -1/4 so now that we know the value of h and k y = a(x - 5/2)^2 - 1/4 to find the value of a, just plug the value of point that's passed by the graph. i'll plug x=1, from the standard form, i'll get y=1-5+6 = 2 then i plug that point (1,2) 2=a(1-5/2)^2 - 1/4 2=a(-3/2)^2 -1/4 2=a(9/4)-1/4 a(9/4) = 9/4 -> a=1 finally we have the complete vertex form y=1(x-5/2)^2 - 1/4 -> y=(x - 5/2)^2 - 1/4
the graph will be looked like this
1 Attachment

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

Not the answer you are looking for?

Search for more explanations.

Ask your own question